WRITER OF INDEPENDENT UKRAINE – OBJECT OF A DISCRETE MOCKERY - MELNYK (KURYLIV), O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article investigates the technique of irony on the examples of short prose by V. Kozhelyanko, O. Irvanets, V. Vrublevskyy, O Stusenko, where the main characters are writers. The discrete position of the author regarding the characters is identified on the basis of the analysis of means of irony.